Adjacent sequences disclose potential for intra-genomic dispersal of satellite DNA repeats and suggest a complex network with transposable elements. (December 2016) - Satović, Eva; Vojvoda Zeljko, Tanja; Luchetti, Andrea; Mantovani, Barbara; Plohl, Miroslav
Abstract Background Satellite DNA (satDNA) sequences are typically arranged as arrays of tandemly repeated monomers. Due to the similarity among monomers, their organizational pattern and abundance, satDNAs are hardly accessible to structural and functional studies and still represent the most obscure genome component. Although many satDNA arrays of diverse length and even single monomers exist in the genome, surprisingly little is known about transition from satDNAs to other sequences. Studying satDNA monomers at junctions and identifying DNA sequences adjacent to them can help to understand the processes that (re)distribute satDNAs and significance that evolution of these sequence elements might have in creating the genomic landscape. Results We explored sets of randomly selected satDNA-harboring genomic fragments in four mollusc species to examine satDNA transition sites, and the nature of adjacent sequences. All examined junctions are characterized by abrupt transitions from satDNAs to other sequences. Among them, junctions of only one examined satDNA mapped non-randomly (within the palindrome), indicating that well-defined sequence feature is not a necessary prerequisite in the junction formation. In the studied sample, satDNA flanking sequences can be roughly classified into two groups. The first group is composed of anonymous DNA sequences which occasionally include short segments of transposable elements (TEs) as well as segments of other satDNA sequences. In the second group, satDNA repeats and the array flanking sequences are identified as parts of TEs of theHelitron superfamily. There, some array flanking regions hold fragmented satDNA monomers alternating with anonymous sequences of comparable length as missing monomer parts, suggesting a process of sequence reorganization by a mechanism able to excise short monomer parts and replace them with unrelated sequences. Conclusions The observed architecture of satDNA transition sites can be explained as a result of insertion and/or recombination events involving short arrays of satDNA monomers and TEs, in combination with hypothetical transposition-related ability of satDNA monomers to be shuffled independently in the genome. We conclude that satDNAs and TEs can form a complex network of sequences which essentially share the propagation mechanisms and in synergy shape the genome.